An Exploratory Pilot Study of Changes in Global DNA Methylation in Patients Undergoing Major Breast Surgery Under Opioid-Based General Anesthesia - Caputi, Francesca Felicia; Carboni, Lucia; Rullo, Laura; Alessandrini, Irene; Balzani, Eleonora; Melotti, Rita Maria; Romualdi, Patrizia; Candeletti, Sanzio; Fanelli, Andrea (Frontiers in Pharmacology, 2021)
This study aimed to investigate DNA methylation levels in patients undergoing major breast surgery under opioid-based general anesthesia. Blood samples were collected from eleven enrolled patients, before, during and after anesthesia. PBMC were isolated and global DNA methylation levels as well as DNA methyltransferase (DNMT) and cytokine gene expression were assessed. DNA methylation levels significantly declined by 26%, reversing the direction after the end of surgery. Likewise, DNMT1a mRNA expression was significantly reduced at all time points, with lowest level of -68%. DNMT3a and DNMT3b decreased by 65 and 71%, respectively. Inflammatory cytokines IL6 and TNFα mRNA levels showed a trend for increased expression at early time-points to end with a significant decrease at 48h after surgery. This exploratory study revealed for the first time intraoperative global DNA hypomethylation in patients undergoing major breast surgery under general anesthesia with fentanyl. The alterations of global DNA methylation here observed seem to be in agreement with DNMTs gene expression changes. Furthermore, based on perioperative variations of IL6 and TNFα gene expression, we hypothesize that DNA hypomethylation may occur as a response to surgical stress rather than to opiate exposure.